1985
DOI: 10.2118/12129-pa
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Foam Flow in Porous Media: Apparent Viscosity in Smooth Capillaries

Abstract: The apparent viscosity of foam flowing through smooth capillaries was measured experimentally, and a mathematical model was developed. Foam texture (a measure of bubble volume) is a key parameter in determining the following properties of foam flowing through a capillary:whether the foam exists as bulk foam or as a chain of bubbles where each pair of bubbles is separated by an individual lamella,the number of lamellae per unit length of the capillary, andthe radius of curvature of the gas-liquid interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
470
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(486 citation statements)
references
References 7 publications
15
470
1
Order By: Relevance
“…Based on the theoretical studies of Bretherton (1961) and Hirasaki and Lawson (1985), the effective viscosity of the non-Newtonian foam is described as…”
Section: Effective Viscosity Of Foammentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the theoretical studies of Bretherton (1961) and Hirasaki and Lawson (1985), the effective viscosity of the non-Newtonian foam is described as…”
Section: Effective Viscosity Of Foammentioning
confidence: 99%
“…In the absence of flowing foam bubbles (i.e., n f = 0), the gas viscosity is recovered. Friedmann et al (1991) reported an empirical value of 0.29 for the exponent c. The Bretherton-based theoretical value is 1/3 (Bretherton 1961;Hirasaki and Lawson 1985;Falls et al 1989). Falls et al (1989) developed a different theoretical model to account for the pore constriction in homogeneous bead packed in glass tubes.…”
Section: Effective Viscosity Of Foammentioning
confidence: 99%
“…The gas relative permeability reduction effect is caused by a large effective trapped gas saturation created by foam. The dragging of flowing lamellae along pore walls leads additional resistance to the flowing of foaming bubbles compared with foam-free gas (Hirasaki and Lawson 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Each vertical film touches both plates along lines called Plateau borders. When sliding on the plates, they induce a viscous dissipation that becomes important even at relatively small velocities [5,6]. When a foam is pushed in the cell, it is thus submitted to a viscous force depending on its velocity and on the density of Plateau borders, ie on the bubble sizes.…”
Section: Introductionmentioning
confidence: 99%